Pengaruh Model Problem Based Learning Berbantuan Media Visual Canva terhadap Hasil Belajar Fisika Peserta Didik - Nila Suhijayani; Sutrio; Jannatin 'Ardhuha (Mataram University, 2026)
This study was motivated by the low physics learning outcomes of students at SMA Negeri 2 Narmada, particularly in the topic of Rotational Dynamics and Rigid Body Equilibrium. Abstract concepts and lecture-dominated teaching methods have caused students to be less active and perceive the material as difficult to understand. This study aims to determine the effect of the problem based learning model assisted by canva visual media on students' physics learning outcomes in the cognitive domain. Data from the affective and psychomotor domains were collected as supporting data to describe students' attitudes and skills during the learning process. This research employed a quasi-experimental method with a Non-equivalent Control Group Design. The sample consisted of 48 eleventh-grade students selected through purposive sampling and divided into an experimental class and a control class. Data were collected using a cognitive test consisting of 20 multiple-choice questions with reasons, and observation sheets for the affective and psychomotor domains. Cognitive data were analyzed using an Independent Samples T-Test and N-Gain test, while affective and psychomotor data were analyzed using descriptive percentages. The results showed a significance value (2-tailed) of 0.000 (p < 0.05), indicating a significant effect of the problem based learning model assisted by Canva on cognitive learning outcomes. Prior to treatment, the experimental and control classes had similar initial abilities with mean pretest score of 43.75 and 45.00, respectively. After treatment, the mean posttest score of the experimental class increased significantly to 81.88, while the control class only reached 56.46. The improvement in cognitive learning outcomes was further demonstrated by the N-Gain test, which showed an average N-Gain score of 0.6897 for the experimental class, categorized as medium, while the control class only achieved 0.2142, categorized as low. Supporting data indicated that the experimental class achieved an average affective score of 82.73% in the very good category and an average psychomotor score of 86.81% in the very skilled category. The implementation of the Problem Based Learning model assisted by canva visual media proved to be effective and significant in improving physics learning.